2011
DOI: 10.1159/000331717
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β<sub>3</sub>-Adrenoceptor Promotes Rapid Pacing-Induced Atrial Electrical Remodeling in Rabbits

Abstract: Cardiac electrophysiological function is under the regulatory control of the sympathetic nervous system. In addition to classical β-adrenoceptors (β-AR, including β1- and β2- subtypes), β3-AR is also expressed in human heart and shows its distinctive functions. This study is aimed to elucidate the role of β3-AR in the regulation of atrial fibrillation (AF), especially its role in rapid pacing-induced atrial electrical remodeling in rabbits. The rapid atrial pacing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Inhibition of β3-AR suppresses AF-induced metabolism-related protein disruption via regulating PPARα/PGC-1α pathway. All of these results, together with our previous reports that β3-AR inhibition could block structural [11] and electrical [10] remodeling and partially alleviate metabolism-related protein remodeling in rodent models, suggest that the β3-AR might be a potential novel target for AF therapy.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…Inhibition of β3-AR suppresses AF-induced metabolism-related protein disruption via regulating PPARα/PGC-1α pathway. All of these results, together with our previous reports that β3-AR inhibition could block structural [11] and electrical [10] remodeling and partially alleviate metabolism-related protein remodeling in rodent models, suggest that the β3-AR might be a potential novel target for AF therapy.…”
Section: Resultssupporting
confidence: 61%
“…We also previously reported that β3-AR activation increases I to in rapidly paced atrial myocytes [10] and reduced AERP. In this study, β3-AR inhibition reversed the AF-induced decrease of AERP also suggests that the PPARα/PGC-1α signaling pathway contributes to the β3-AR-mediated metabolism remodeling.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations